Preservation of mandarins using a microbial decontamination system integrating calcium oxide solution washing, modified atmosphere packaging, and dielectric barrier discharge cold plasma treatment. (September 2021) - Bang, In Hee; Kim, Ye Eun; Min, Sea C.
Graphical abstract: Highlights: CaO washing-MAP-plasma combination effectively decontaminates mandarins. CaO washing or MAP increases the inactivation efficiency of plasma treatment (PT). CaO washing-MAP-PT combination minimizes the deterioration of fruits during storage. Use of this technology is anticipated to extend the shelf life of citrus fruits. Abstract: A new microbial decontamination system integrating with calcium oxide solution washing (CaOW), packaging in modified atmosphere (MAP), and treatment with dielectric barrier discharge cold plasma (CPT) was developed and its effects on mandarin storability were investigated. CPT was applied for 2 min at 27 kV to mandarins, formerly prepared with and without CaOW for 3 min and packaged with air or O2 -CO2 -N2 (9.9, 2.1, and 88.0%, respectively). CaOW-CPT effectively retarded the decrease in the ascorbic acid concentration and antioxidant capacity of mandarin flesh at 4 °C and 25 °C, and its total phenolic content (TPC) at 25 °C. Modified atmosphere more effectively delayed the increase in the concentration of CO2, generated by mandarins at 4 °C and 25 °C and the decrease in flesh TPC at 4 °C than air-packaging ( p < 0.05). Both CaOW and MAP increased the efficiency of CPT in inhibiting Penicillium digitatum growth, immediately after treatment and during storage at 25 °C. The microbial decontamination system integrating CaOW, MAP, and CPT effectively retarded the decrease in ascorbic acid concentration and antioxidant activity of the flesh during storage at 4 °C and 25 °C, without influencing the pH and color of mandarins at both temperatures. This study demonstrated the technological potential of the microbial decontamination system combining CaOW, MAP, and CPT for extending the shelf life of mandarins.